Worlds of Print: The Moral Imagination of an Informed Citizenry, 1734-1835 - Slifko, John P. (Editorial de la Sede del Pacífico de la Universidad de Costa Rica, 2016)
The researcher John P. Slifko has defended a thesis and finalized the full dissertation on November 15, 2015, entitled Worlds of Print: The Moral Imagination of an Informed Citizenry, 1734-1835 at the University of California, Los Angeles in the United States of America.